Numerical modeling of gas production from methane hydrate deposits using low-frequency electrical heating assisted depressurization method. (15th April 2021) - Zhao, Ermeng; Hou, Jian; Du, Qingjun; Liu, Yongge; Ji, Yunkai; Bai, Yajie
Graphical abstract: Highlights: A mathematical model of low-frequency electrical heating assisted depressurization (LF-EHAD) method is established. The energy recovery behaviors from hydrate deposits with LF-EHAD are analyzed. Gas production is significantly enhanced by electrical heating with a high energy efficiency ratio of 9.65. The LF-EHAD method shows better production performance than hot water flooding. Abstract: With the increasing global demand for clean energy, methane hydrate has been regarded as a potential alternative energy source in future due to its huge resources and high energy density. In this study, a mathematical model is established to evaluate the production performance of low-frequency electrical heating assisted depressurization (LF-EHAD) method for hydrate deposits recovery. Within the framework of this model, the integral finite difference method and Newton-Raphson iteration are employed for solution, which is then validated by the experiment data. Using this model, the energy recovery behaviors with LF-EHAD from Shenhu hydrate deposits are investigated and then compared with those performed by hot water flooding and depressurization. Simulation results show that hydrate dissociation and gas production are significantly enhanced as a result of sufficient heat supplied by the electrical heating, validating the potential of the LF-EHAD for hydrate deposits recovery. After 2000 days of production, the cumulative gas production of LF-EHAD and hot water injection are 2.37 times and 1.47 times of that conducted by the depressurization method. Moreover, the heat consumption used to increase the formation temperature in the hydrate dissociation region under LF-EHAD is much less than that of hot water flooding, which results in a higher energy efficiency ratio (EER) of 9.65 for LF-EHAD, while the EER of hot water flooding is 4.42. Overall, LF-EHAD shows better performance than hot water flooding with the same amount of heat input because of higher gas production and energy utilization efficiency, but lower water production.